Improved retention of ocular prosthesis with modified shallow socket impression technique - sinulingga, Andri; Putri Welda Utami Ritonga; Haslinda Z. Tamin (Indonesian Journal of Prosthodontic, 2024)
ABSTRACT Background: The long-term use of a custom ocular prosthesis that is not replaced could cause a shallow socket. These changes affect the size of the socket. In fact, the custom ocular prosthesis becomes loose. Objectives: Modify the impression by duplicating the old custom ocular prosthesis as a special tray for obtaining an accurate impression of the socket and reducing clinical visits. Case Report:. A 42-year-old woman came to Dental Hospital Universitas Sumatera Utara with the chief complaint that the custom ocular prosthesis was easy to fall off and painful during movement. She has worn the ocular prosthesis for over 30 years, fabricating it five times. However, the last ocular prosthesis lasted for 10 years. The definitive impression was prepared by duplicating the custom ocular prosthesis, and this special tray was modified by adding a rod with a light body material due to its low viscosity. As a result of using the special tray, a more accurate impression can be made due to the small size of the rod. Conclusion: The impression technique with a modified tray from the duplicated old custom ocular prosthesis can record the eye socket in detail and produces a retentive custom ocular prosthesis.